2020
DOI: 10.1016/j.heliyon.2020.e03879
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the determinants of GIT post-adoption: perspectives from Mozambican institutions

Abstract: This study aims to understand the determinants of geographical information technologies at the scale of postadoption use and intention to increase the level of use in Mozambican institutions. Three known theories (diffusion of innovation theory, technologyorganisationenvironment framework, and institutional theory) have been used in order to accomplish the study. The data analysis showed that the variables compatibility, geographical scope, expansion opportunities, and normative pressure contribute to explaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…Amade et al [59] found that CP arises from effects that originate from the structural or legal mandates on which the focal firm is reliant. Considering the adoption of IT/IS at the organizational level, CP exerted by government regulatory bodies on innovations/technologies may extensively influence IT/IS adoption [26,42].…”
Section: Coercive Pressure and Erp Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amade et al [59] found that CP arises from effects that originate from the structural or legal mandates on which the focal firm is reliant. Considering the adoption of IT/IS at the organizational level, CP exerted by government regulatory bodies on innovations/technologies may extensively influence IT/IS adoption [26,42].…”
Section: Coercive Pressure and Erp Adoptionmentioning
confidence: 99%
“…The majority of earlier studies have overlooked the examination of environmental forces of NP in ERP adoption within SMEs; the few empirical works conducted in this domain have assured the importance of NP in IS adoption process within institutional firms [41,42,59]. Ahmadi et al [63] studied the adoption of Hospital Information Systems (HISs) within the context of an organization.…”
Section: Normative Pressure and Erp Adoptionmentioning
confidence: 99%
“…Based on these reasons, it can be understood why compatibility is not a concern among government agencies because responding to the national agenda is more necessary. Within the same tones, Amade, et al [ 149 ] and Junior, et al [ 129 ] asserted that the compatibility of innovation is not statistically significant in the post-adoption phase. Amade, et al [ 149 ] confirmed whether compatibility influences Mozambican institutions in an effort to continue using geographical information technologies.…”
Section: Discussionmentioning
confidence: 98%
“…Within the same tones, Amade, et al [ 149 ] and Junior, et al [ 129 ] asserted that the compatibility of innovation is not statistically significant in the post-adoption phase. Amade, et al [ 149 ] confirmed whether compatibility influences Mozambican institutions in an effort to continue using geographical information technologies. In contrast, Junior, et al [ 129 ] emphasized that compatibility has no positive influence on enterprise resource planning diffusion among farmers in Brazil.…”
Section: Discussionmentioning
confidence: 98%
“…The more it is perceived, the more rapid its rate of adoption is going to be); ( 2) Compatibility (the degree to which an innovation is perceived to be consistently taking into consideration existing values); (3) Complexity (the degree to which an innovation is perceived as challenging to understand and use. Simple ideas will be adopted more rapidly); ( 4) Trialability (the degree to which an innovation may be tested on a limited basis); (5) Observability (the degree to which the results of an innovation are visible to others) [18].…”
Section: Diffusion Of Innovation Theory(dit)mentioning
confidence: 99%